Essential oil from Sabina chinensis leaves: A promising green control agent against Fusarium sp. - Zhang, Jianyun; Zhao, Ziyi; Liang, Wenyu; Bi, Jingyi; Zheng, Yuguang; Gu, Xian; Fang, Huiyong (Frontiers in Plant Science, 2022)
Sabina chinensis is a woody plant with important ecological functions in different regions of China, but its essential oils (EO) against plant pathogenic fungi remain largely undetermined. The purpose of our study was to assess the chemical composition and antifungal activity of S. chinensis EO based on optimization of the extraction process. In this study, an actionable and effective model with the experimental results and identified optimum conditions (crushing degree of 20 mesh, liquid‒solid ratio of 10.1:1, immersion time of 9.1 h) was established successfully to achieve an extraction yield of 0.54%, which was basically consistent with the theoretical value. A total of 26 compounds were identified using headspace gas chromatography‒mass spectrometry (GC‒MS) and showed that the major constituent was β-phellandrene (26.64-39.26%), followed by terpinen-4-ol (6.53-11.89%), bornyl acetate (6.13-10.53%), etc. For Petri plate assays, our experiments found for the first time that S. chinensis EO revealed high and long-term antifungal activity against the tested strains, including Fusarium oxysporum and Fusarium incarnatum, at EC50 values of 1.42 and 1.15 µL/mL, which especially reached approximately 76% and 90% growth inhibition at a dose of 0.2 µL/mL, respectively. Furthermore, the antifungal activity of EO from different harvest periods showed remarkable variation. The orthogonal partial least-squares discriminant analysis (OPLS-DA) method revealed 11 metabolites with chemical marker components, and 5 of its potential antifungal activities, terpinen-4-ol, α-terpineol, α-elemol, γ-eudesmol, and bornyl acetate, were strongly correlated with the mycelial inhibition rate. In total, this study explored the antifungal activity of EO against root rot fungus as a potential fungicide and provided valuable information into developing potential products from natural agents.